Transgenic Eimeria magna Pérard, 1925 Displays Similar Parasitological Properties to the Wild-type Strain and Induces an Exogenous Protein-Specific Immune Response in Rabbits (Oryctolagus cuniculus L.) - Tao, Geru; Shi, Tuanyuan; Tang, Xinming; Duszynski, Donald W.; Wang, Yunzhou; Li, Chao; Suo, Jingxia; Tian, Xiuling; Liu, Xianyong; Suo, Xun (Frontiers in Immunology, 2017)
Rabbit coccidiosis causes great economic losses to world rabbitries. Little work has been done considering genetic manipulation on the etiological agents, rabbit Eimeria spp. In this study, we constructed a transgenic line of Eimeria magna (EmagER) expressing enhanced yellow fluorescent protein (EYFP) and red fluorescent protein (RFP) using regulatory sequences of Eimeria tenella and Toxoplasma gondii. We observed the life cycle of EmagER and confirmed that the transgenic parasites express exogenous proteins targeted to different cellular compartments throughout the entire life cycle. EYFP was expressed mainly in the nucleus and RFP both in the nucleus and cytoplasm. Then, coccidia-free, laboratory-reared 40-day-old rabbits were primarily infected with either EmagER or wild-type strain oocysts and challenged with the wild-type strain. EmagER showed similar reproductivity and immunogenicity to the wild-type strain. Finally, we examined the foreign protein-specific immune response elicited by EmagER. Rabbits were immunized with either transgenic or wild-type oocysts. Immune response against parasite-soluble antigen, EYFP and RFP in spleen, and mesenteric lymph nodes were detected by quantitative real-time PCR. The relative expression level of IFN-γ, IL-2, and TNF-α were higher in EmagER-immunized rabbits than wild-type parasites-immunized rabbits after stimulation with EYFP and RFP. Our study confirmed that a specific immune response was induced by the exogenous protein expressed by EmagER and favored future studies on application of transgenic rabbit coccidia as recombinant vaccine vectors.